GEOGRAFIA DO FUTEBOL DAS CIDADES MÉDIAS BRASILEIRAS: RELAÇÕES ENTRE SUCESSO ESPORTIVO E CARACTERÍSTICAS URBANAS (Terr@ Plural, 2019)
Football is an intra-urban element and a constructor of the relationship among cities, however in Brazil there are few studies about this theme, especially in medium-sized cities. Thus, we analyzed the relations between soccer success and the characteristics of 70 Brazilian medium-sized cities, regional capitals. We found that soccer develops heterogeneously: clubs in medium-sized cities in the South and Southeast tend to perform better; being in the capital does not influence results directly; there is a positive relationship between urban hierarchy and soccer success, despite exceptions; there is no relation between demographic size and sports results; there is a positive relationship between GDP and soccer success.